The UI/UX development of the 'Koin' application to create interactive Korean language learning - Alfira Faza Aprilia; Didin Samsudin; Arif Husein Lubis (Inovasi Kurikulum, 2024)
With the rapid development of technology, there is an excellent opportunity to utilize it in creating interactive, application-based Korean language learning media. This study aims to design the 'Koin' application, primarily focusing on its UI and UX aspects, to enhance effectiveness and user engagement in Korean language learning. This research employs the design thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. Data for this study were collected through qualitative and quantitative methods, including structured interviews and usability testing with beginner-level Korean language learners as participants. Two media experts and two subject matter experts in the Korean language were engaged to provide feedback and suggestions to ensure the validity of the developed application. The qualitative results demonstrate that the design thinking method has identified the user’s needs in-depth and captured the user’s good experience navigating the interface with relevant features. The quantitative results show that the UI/UX design of the Korean language learning application for beginners, developed using the design thinking method, resulted in a well-designed application with a final score of 80 points. This finding indicates that design thinking effectively designs learning applications that meet target users' needs and preferences.   Abstrak Dengan perkembangan teknologi yang sangat pesat, terdapat peluang besar untuk memanfaatkannya dalam menciptakan media pembelajaran bahasa Korea berbasis aplikasi yang interaktif. Penelitian ini bertujuan untuk merancang aplikasi 'Koin', dengan fokus utama pada UI dan UX untuk meningkatkan efektivitas dan keterlibatan pengguna dalam pembelajaran bahasa Korea. Penelitian ini menggunakan metode design thinking, yang terdiri dari lima tahap: empathize, define, ideate, prototype, dan test. Data untuk penelitian ini dikumpulkan dengan menggunakan metode kualitatif dan kuantitatif, termasuk wawancara terstruktur dan uji kegunaan dengan pemelajar bahasa Korea tingkat pemula sebagai partisipan. Selain itu, dua ahli media dan dua ahli materi pelajaran bahasa Korea juga dimintai pendapat untuk memberikan masukan serta saran untuk memastikan validitas aplikasi yang dikembangkan. Hasil kualitatif menunjukkan bahwa metode design thinking telah mengidentifikasi secara mendalam dan menggambarkan pengalaman positif pengguna pada navigasi antarmuka dengan fitur-fitur yang relevan. Hasil kuantitatif mengindikasikan bahwa desain UI/UX aplikasi pembelajaran bahasa Korea untuk pemula yang dikembangkan dengan metode design thinking menghasilkan aplikasi yang dirancang dengan baik dan mendapatkan skor akhir 80 poin. Temuan ini menunjukkan bahwa pendekatan design thinking efektif dalam merancang aplikasi pembelajaran yang sesuai dengan kebutuhan dan preferensi target pengguna. Kata Kunci: antarmuka pengguna; aplikasi pembelajaran bahasa Korea; design thinking; pengalaman pengguna